Application of Caillou auf Deutsch Cartoon Movie Based on Paired Storytelling Method to Train Speaking Skills in Conversation II Course - Nurkarimah, Diyah; Widyatmoko, Tiksno (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This study aims to describe the application of Caillou Deutsch cartoon based on Paired Storytelling method in practicing speaking skills in Conversation II course. This study used descriptive qualitative approach with research instruments in the form of observation guidelines and tests. The results showed that students were active in the learning process and able to speak fluently. Students' response to the use of cartoons is very enthusiastic; they consider this learning media exciting and fun, and actively speak in front of the class. In addition, the application of Caillou Deutsch cartoons based on the Paired Storytelling method showed good learning outcomes, where the majority of students obtained good scores in three aspects of assessment. This study also helped students enrich their vocabulary and express themselves through paired communication with classmates. Based on these findings, it can be concluded that Caillou Deutsch cartoon based on Paired Storytelling method is an effective learning media in practicing German speaking skills.